Qualität in der Inhaltserschließung - Franke-Maier, Michael; Kasprzik, Anna; Ledl, Andreas; Schürmann, Hans (Bibliotheks- und Informationspraxis, 2021)
This edited volume deals with issues relating to the quality of subject cataloging in the digital age, where heterogenous articles from different processes meet, and attempts to define important quality standards. Topics range from metadata and the cataloging policies of the German National Library, the GND, and the head offices of the German library association, to the presentation of a range of different projects, such as QURATOR and SoNAR.